A miniaturized circularly polarized coaxial fed superstrate slot antenna for L‐band application. Issue 6 (29th January 2018) - Ali, Tanweer; Saadh, Mohammad A. W.; Pathan, Sameena; Biradar, Rajashekhar C.
Abstract : A miniaturized circularly polarized superstrate antenna is presented in this letter. The antenna consists of a corner cut square radiating patch in which 4 arrow type slots are etched out, a superstrate placed exactly above the radiating patch and a coaxial feed. Circular polarization in the design is accomplished by the corner cuts in the radiating patch and placing the feed point below origin (0, 0, 0) along x‐axis. The slot miniaturization technique results in about 73.7% and 79.8% reduction in volume and active patch area of the designed antenna. The antenna has a compact dimension of about0.11λ 0 × 0.11λ 0 × 0.02λ 0 at a frequency of 1.21 GHz with S 11 < − 10 dB bandwidth of about 3.03% (1.30–1.34 GHz). Axial ratio < 3, good impedance matching, acceptable gain, radiation efficiency greater than 90%, and stable radiation characteristics are observed across the operational bandwidth of the designed antenna.